Mathematical Communication Skills of Junior High School Students with High Mathematical Resilience on Opportunity Materials - Adinda Juniasani; Sutrisno Sutrisno; Agnita Siska Pramasdyahsari (Urogram Studi Pendidikan Matematika, Universitas IVET, 2022)
This study aims to describe the mathematical communication skills of junior high school students with high mathematical resilience on the material of probability. The subjects selected in this study were two students of class VIII I of SMP N 1 Sulang who had high mathematical resilience. Data collection techniques used are mathematical resilience questionnaires, written tests and interviews. The validity of the research data was tested using technical triangulation, source triangulation and time triangulation. Data processing and analysis of research results are assisted by the Nvivo QSR software. The results of this study indicate that students with high mathematical resilience can master all indicators to the maximum. Students are able to express mathematical ideas through writing and orally. Students are also able to demonstrate, describe, and understand mathematical ideas. In addition, students are also able to evaluate and interpret mathematical ideas. Students have also used mathematical notations in working on problems on probability material. Keywords: mathematical communication, mathematical resilience, probability material.